2015
DOI: 10.4067/s0718-58392015000200007
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia treatment on germinating faba bean (Vicia faba L.) seeds enhances GABA-related protection against salt stress

Abstract: The γ-aminobutyric acid (GABA) is a non-protein amino acid with some functional properties for human health. Its content is usually lower in plant seeds. Hypoxia or salt (NaCl) stress is an effective way for accumulating GABA during seed germination. However, NaCl stress on GABA accumulation under hypoxia is currently infrequent. The effect of NaCl on GABA accumulation in germinating faba bean (Vicia faba L.) under hypoxia was therefore investigated in this study. Faba bean seeds were steeped in citric acid bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As a signal molecule, GABA plays a key role in the response of plants to external stimuli. Under salt stress, GABA accumulated in germinated soybean [ 4 ], faba bean [ 26 ], and brown rice [ 27 ]. At the same time, GABA promoted the synthesis of phenolics under NaCl stress (60 mmol L −1 ) in barley seedlings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a signal molecule, GABA plays a key role in the response of plants to external stimuli. Under salt stress, GABA accumulated in germinated soybean [ 4 ], faba bean [ 26 ], and brown rice [ 27 ]. At the same time, GABA promoted the synthesis of phenolics under NaCl stress (60 mmol L −1 ) in barley seedlings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…salt stress) can increase the level of GABA in plants . Yang et al . reported that this phenomenon depends on stress intensity and duration.…”
Section: Effect Of Pulse Processing On Gabamentioning
confidence: 99%
“…These authors suggested that the longer stress treatment may have destroyed the activity of the enzymes responsible for GABA production (e.g. GAD and DAO) . The addition of a second stressor modified the level of GABA production in the faba beans.…”
Section: Effect Of Pulse Processing On Gabamentioning
confidence: 99%
“…In faba beans, the effects of hypoxia and salinity were analyzed separately, on root development for hypoxia [23] and on the physiological and biochemical response of the whole plant for salinity [24]. Few studies analysed the double hypoxia-NaCl stress on γ-aminobutyric acid accumulation [25,26], but no study has analyzed the effects of the double constraint on growth parameters. The selection of legume genotypes with better tolerance to hypoxia and salinity is therefore an important agronomic objective to allow more efficient use of legumes either alone or in rotation with other crops.…”
Section: Introductionmentioning
confidence: 99%